Conservation of genetic uniqueness in remaining populations of red squirrels (Sciurus vulgaris L.) in the South of England. Issue 11 (24th May 2019) - Hardouin, Emilie A.; Baltazar‐Soares, Miguel; Schilling, Anna‐Katarina; Butler, Helen; García‐Rodríguez, Oxala; Crowley, Eloise; Liang, Wei‐Jun; Meredith, Anna; Lurz, Peter W. W.; Forster, Jane; Kenward, Robert E.; Hodder, Kathy H.
Abstract: The Eurasian red squirrel ( Sciurus vulgaris ) is an emblematic species for conservation, and its decline in the British Isles exemplifies the impact that alien introductions can have on native ecosystems. Indeed, red squirrels in this region have declined dramatically over the last 60 years due to the spread of squirrelpox virus following the introduction of the gray squirrel ( Sciurus carolinensis ). Currently, red squirrel populations in Britain are fragmented and need to be closely monitored in order to assess their viability and the effectiveness of conservation efforts. The situation is even more dramatic in the South of England, where S. vulgaris survives only on islands (Brownsea Island, Furzey Island, and the Isle of Wight). Using the D‐loop, we investigated the genetic diversity and putative ancestry of the squirrels from Southern England and compared them to a European dataset composed of 1, 016 samples from 54 populations. We found that our three populations were more closely related to other squirrels from the British Isles than squirrels from Europe, showed low genetic diversity, and also harbored several private haplotypes. Our study demonstrates how genetically unique the Southern English populations are in comparison with squirrels from the continental European range. We report the presence of four private haplotypes, suggesting that these populations may potentially harbor distinct genetic lineages. Our results emphasize the importance of preserving these isolated red squirrel populations for the conservation of the species. Abstract : Our study demonstrates how genetically unique the Southern English populations are in comparison with squirrels in the non‐threatened European range. We report the presence of four private haplotypes, suggesting that these populations may potentially harbour distinct genetic lineages. Our results emphasise the importance of preserving these isolated red squirrel populations for the conservation of the species.